A Hiatus Obscures the Early Evolution of Modern Lineages of Bony Fishes - Romano, Carlo (Frontiers in Earth Science, 2021)
About half of all vertebrate species today are ray-finned fishes (Actinopterygii), and nearly all of them belong to the Neopterygii (modern ray-fins). The oldest unequivocal neopterygian fossils are known from the Early Triassic. They appear during a time when global fish faunas consisted of mostly cosmopolitan taxa, and contemporary bony fishes belonged mainly to non-neopterygian (‘palaeopterygian’) lineages. In the Middle Triassic (Pelsonian substage and later), less than 10 myrs (million years) after the Permian-Triassic boundary mass extinction event (PTBME), neopterygians were already species-rich, and bony fish faunas were more regionally differentiated compared to the Early Triassic. Still little is known about the early evolution of neopterygians leading up to this first diversity peak. A major factor limiting our understanding of this ‘Triassic revolution’ is an interval marked by a very poor fossil record, overlapping with the Spathian (late Olenekian, Early Triassic), Aegean (Early Anisian, Middle Triassic), and Bithynian (early Middle Anisian) substages. Here, I review the fossil record of Early and Middle Triassic marine bony fishes (Actinistia and Actinopterygii) in order to evaluate the impact of this hiatus – named herein the Spathian–Bithynian gap (SBG) – on our understanding of their diversification after the largest mass extinction event of the past. I propose three hypotheses: (1) the SSBE hypothesis, suggesting that most of the Middle Triassic diversity appeared in the aftermath of the Smithian-Spathian boundary extinction (SSBE; ~2 myrs after the PTBME), (2) the Pelsonian explosion hypothesis, which states that most of the Middle Triassic diversity is the result of a radiation event in the Pelsonian, and (3) the gradual replacement hypothesis, i.e. that the faunal turnover during the SBG was steady and bony fishes were not affected by extinction events subsequent to the PTBME. Based on current knowledge, hypothesis 3 is favored herein, but further studies are necessary to test alternative hypotheses. In light of the SBG, claims of a protracted diversification of bony fishes after the PTBME should be treated with caution.